Cultural and Political Imaginaries in Putin's Russia - Bernsand, Niklas; Törnquist-Plewa, Barbara (Eurasian Studies Library, 2018)
The developments in Russian official symbolical, cultural and social policies as well as the contradictory trajectories of important cultural, social and intellectual trends in Russian society after the year 2000. Readership: The book is intended for specialists as well as for undergraduate and postgraduate students in the fields of politics, culture and society in Russia and other Post-Soviet countries, cultural policy, memory, history, Putin, ideology, nationalism, political regimes, elites, grassroots, Post-Soviet politics, social media, social movements, intellectual history, and imperial visions.